Improving Frontliner Performance through Digital Financial Literacy Strategy - Sidik Nusannas, Iman; Sojanah, Janah; Koku Dabi, Rowland Seyram; Yusuf Maulana, Dede (Jurnal Ekuisci, 2024)
This study aims to develop a plan for increasing staff performance at a private bank in Bandung by promoting financial digital literacy. 242 frontliners were chosen as the sample via proportionate random selection for this quantitative descriptive study. Data were evaluated using the AMOS 24 Structural Equation Model (SEM). The findings demonstrated that self efficacy, engagement, and ability all have a positive and significant impact on frontline workers' performance, with digital financial literacy serving as an effective intermediary. Based on the study's findings, a private bank performance improvement model that combines self-efficacy, employee engagement, ability, and financial digital literacy has been identified.